Comprehensive phenotyping of 1,807 Indian barnyard millet (Echinochloa frumentacea Link) accessions from Indian national genebank: unlocking diversity for core set development - Singh, Badal; Pandey, Sushil; Nivedhitha, S.; Shekhawat, Neelam; Singh, Mamta; Jat, Balram; Pandey, Chithra Devi; Semwal, D. P.; Arya, Lalit; Gautam, R. K.; Singh, G. P. (Frontiers in Plant Science, 2025)
IntroductionA comprehensive characterization of 1,807 barnyard millet (Echinochloa frumentacea Link.) accessions conserved in the Indian National Genebank (INGB) was conducted to assess genetic variability and develop a representative core set.MethodsThirteen qualitative and ten quantitative traits were evaluated. Five core sets were created using Core Hunter 3, utilizing optimization approaches to enhance representativeness and diversity. Comparisons were made between the entire collection and the developed core sets using diversity indices, statistical parameters, correlation analysis, and principal component analysis (PCA).ResultsSignificant diversity was revealed across traits. Predominant qualitative traits included pyramidal inflorescence shape (89%), green inflorescence color (57%), and intermediate inflorescence compactness (46%). Plant height ranged from 72.36 to 213.96 cm, inflorescence length from 6.73 to 35.65 cm, and 1000-seed weight from 1.01 to 5.55 g, demonstrating a wide range of quantitative characteristics. High heritability values (82.08–94.42%) and substantial genetic advances highlighted their agronomic importance. Among the five cores, core set-3 comprising 271 accessions achieved the best balance of genetic diversity, trait representativeness, and low redundancy, with a variable rate of coefficient of variance (VR) of 110.41%, coincidence rate (CR) of 85.97%, and mean difference percentage (MD) of 30%. Shannon–Weaver diversity indices and evenness values confirmed superior diversity representation. Comparisons showed non-significant differences in means, variances, and frequency distributions for most traits between the core and entire collection. Correlation and PCA confirmed conservation of trait associations and genetic structure, with the first five principal components explaining 74.9% of total variance in the core set, closely aligning with the entire collection (70.8%).ConclusionThis study highlights the utility of the INGB barnyard millet core set as a valuable genetic resource for breeding programs. The core set provides opportunities for the effective use and preservation of barnyard millet genetic resources by improving access to genetically diverse and agronomically significant germplasm.